Data manipulation in an XML-based digital image library - Chang, Naicheng (Program : electronic library and information systems, 2005)
Purpose - To help to clarify the role of XML tools and standards in supporting transition and migration towards a fully XML-based environment for managing access to information.Design methodology approach - The Ching Digital Image Library, built on a three-tier architecture, is used as a source of examples to illustrate a number of methods of data manipulation for presentation processing. An SQL relational database is implemented in the data tier and Microsoft Internet Information Server (IIS) is used to manage processes and sessions in the middle tier. Extensible Markup Language (XML) is used in the data tier to represent offers and in the presentation tiers to represent screen displays that can be manipulated using the XML Document Object Model (DOM), XML Data Islands, and XSL (eXtensible Stylesheet Language), before being delivered to the web browser as HTML.Findings - It is demonstrated that, although XML itself is not a database, the XML family provides many, though not all, of the components found in databases. XML coupled with a database gives greater power than the sum of the parts in a web application.Originality value - This paper is a digital image library case study with practical generic tutorial elements about the role and function of XML in modern database-backed web sites.